Internet‐based therapy versus face‐to‐face therapy for alcohol use disorder, a randomized controlled non‐inferiority trial. (13th October 2020) - Johansson, Magnus; Sinadinovic, Kristina; Gajecki, Mikael; Lindner, Philip; Berman, Anne H.; Hermansson, Ulric; Andréasson, Sven
Abstract: Background and aims: Most people with alcohol use disorder (AUD) are never treated. Internet‐based interventions are effective in reducing alcohol consumption and could help to overcome some of the barriers to people not seeking or receiving treatment. The aim of the current study was to compare internet‐delivered and face‐to‐face treatment among adult users with AUD. Design: Randomized controlled non‐inferiority trial with a parallel design, comparing internet‐delivered cognitive–behavioural therapy (ICBT) ( n = 150) with face‐to‐face CBT ( n = 151), at 3‐ and 6‐month follow‐ups. Setting: A specialized clinic for people with AUD in Stockholm, Sweden. Participants were recruited between 8 December 2015 and 5 January 2018. Participants: A total of 301 patients [mean age 50 years, standard deviation (SD) = 12.3] with AUD, of whom 115 (38%) were female and 186 (62%) were male. Intervention and comparator: Participants were randomized in blocks of 20 at a ratio of 1 : 1 to five modules of therapist‐guided ICBT or to five modules of face‐to‐face CBT, delivered over a 3‐month period. The same treatment material and the same therapists were used in both groups. Measurements: The primary outcome was standard drinks of alcohol consumed during the previous week at 6‐month follow‐up, analysed according to intention‐to‐treat. The pre‐specified non‐inferiority limit was five standard drinks of alcohol and d = 0.32 for secondary outcomes. Results: The difference in alcohol consumption between the internet and the face‐to‐face group was non‐inferior in the intention‐to‐treat analysis of data from the 6‐month follow‐up [internet = 12.33 and face‐to‐face = 11.43, difference = 0.89, 95% confidence interval (CI) = −1.10 to 2.88]. The secondary outcome, Alcohol Use Disorder Identification Test score, failed to show non‐inferiority of internet compared with face‐to‐face in the intention‐to‐treat analysis at 6‐month follow‐up (internet = 12.26 and face‐to‐face = 11.57, d = 0.11, 95% CI = –0.11 to 0.34). Conclusions: Internet‐delivered treatment was non‐inferior to face‐to‐face treatment in reducing alcohol consumption among help‐seeking patients with alcohol use disorder but failed to show non‐inferiority on some secondary outcomes.